Exercise and Carotid Properties in the Young–The KiGGS-2 Study - Königstein, Karsten; Büschges, Julia Charlotte; Sarganas, Giselle; Krug, Susanne; Neuhauser, Hannelore; Schmidt-Trucksäss, Arno (Frontiers in Cardiovascular Medicine, 2022)
Background: Carotid intima-media thickness (cIMT) and stiffness (cS) are predictive markers of early vascular aging and atherosclerotic risk. This study assessed, whether exercise has protective effects on carotid structure and function or on vascular risk in the young. Methods: Volume and change of exercise (recreational and organized sports participation) of German adolescents and young adults was assessed within the prospective population-study KiGGS at KiGGS-Wave-1(2009-2012) and KiGGS-Wave-2(2014-2017) using standardized self-reporting questionnaires. CIMT and cS were measured by real-time B-mode ultrasound sequences with semi-automated edge-detection and automatic electrocardiogram-gated quality control in 2,893 participants (14–28 years, 49.6% female). A cumulative index for atherosclerotic risk (CV-R) included z-scores of mean arterial pressure, triglycerides, total/HDL-cholesterol-ratio, body mass index and HbA1c. Results: At KiGGS-Wave-2 cross-sectional CV-R but not cS and cIMT was lower in all exercise-groups compared to “no exercise” (B=-0.73, 95%-CI=-1.26–0.19, p=0.008). Longitudinal volume of exercise was negatively associated with CV-R (B=-0.37, 95%-CI=-0.74–0.00, p=0.048) but not with cS and cIMT. Cross-sectional relative risk of elevated CV-R but not cS and cIMT was lower in all exercise-groups compared to “no exercise” (RR=0.80, 95%-CI=0.66–0.98, p=0.033). High exercise volumes were associated with lower relative risk of elevated CV-R (RR=0.80, 95%-CI=0.65–0.97, p=0.021) and cS in tendency but not with cIMT. Conclusions: Increased levels of exercise are associated with a better cardiovascular risk profile in young individuals, but not with cS and cIMT. Our study confirms previous recommendations on exercise in this age group without demonstrating a clear benefit on surrogate markers of vascular health.